The performance and limitation of T-SPOT.TB for the diagnosis of TB in a high prevalence setting - Zhu, Changtai; Liu, Zhonghua; Li, Zhiqiang; Mei, Shencong; Hu, Zhongyi (Journal of Thoracic Disease, 2014)
Background: Tuberculosis (TB) diagnosis remains difficulty. The previous reports have shown that the T-SPOT.TB assay may be a more promising diagnostic tool for TB, however, it needs a further study to evaluate the diagnostic value of T-SPOT.TB for the specific populations in a high prevalence setting. Methods: In this present study, we conducted stratified and comparable analyses to explore the clinical value and the limitation of T-SPOT.TB assay in TB diagnosis in a high TB prevalence setting, Southern China. A total of 413 subjects including 163 pulmonary TB (PTB), 39 extrapulmonary TB (EPTB), 106 non-TB pulmonary diseases (NTBPDs), 20 medical staff and 85 healthy controls were included in the study. Results: According to T-SPOT.TB, there had a high incidence of latent TB infection (LTBI) in general population in Southern China, especially in the NTBPDS and medical staff. The T-SPOT.TB had a high performance in the diagnosis of active TB (ATB) in a lower risk of TB infection population such as the general population, however, the T-SPOT.TB for the diagnosis of ATB in the high risk of TB infection populations involving close contacts such as the patients with pulmonary diseases (PD) or medical staff isn’t reliable due to the interference by LTBI. Under this condition, the value of rule-out of the assay was seemed to be better than that of rule-in. We believed that the T-SPOT.TB is suitable for screening both the EPTB and the ATB combined with diabetes mellitus (DM). However, we found that the sensitivity of T-SPOT.TB in sputum smear-negative population wasn’t as high as that in smear-positive population. Conclusions: The T-SPOT.TB testing results should be interpreted with caution combined with subject’s characteristics in a high prevalence setting.